Rastlinski pripravki za lajšanje simptomov menopavze - Gregorič, Klara (Farmacevtski vestnik, 2021)
Menopause is characterised by typical symptoms that arise due to the altered hormone balance. Hot flushes, insomnia and labile moods can affect the quality of life of menopausal women. Usually, hormone replacement therapy is prescribed to alleviate extreme menopausal symptoms, although recently plant products have gained more interest. Most medicinal plants that are meant to reduce menopausal symptoms are sold as dietary supplements; however, there are two herbal medicinal products that are avaliable over the counter in Slovenia. Here we present data on effectiveness, safety and mechanisms of action of herbal preparations that are most commonly used in products for the alleviation of menopausal symptoms.
Keywords: faitoestrogeni; menopause; menopavza; phytoestrogens; plants; rastline